A Facile and Sensitive Electrochemical Analysis Based on Flower-Like Nanocomposite Supported Teicoplanin as the Recognition Element for Tyrosine Enantiomers. Issue 6 (1st January 2019) - Song, Jinyi; Ran, Peiyao; Mo, Fangjing; Wu, Jingling; Fu, Yingzi
Abstract : A facile and sensitive chiral analysis for the recognition of tyrosine (Tyr) enantiomers has been designed based on teicoplanin (Tei) and a flower-like nanocomposite which consisted of copper-platinum core-shell microspheres and single-walled carbon nanotubes-molybdenum disulfide (Cu@Pt/SWCTNs-MoS2 ). The flower-like nanocomposite was employed to improve the immobilization of the chiral selector Tei and the electrochemical performance. The nanocomposite was characterized via scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray (EDX), Raman spectrum, fourier transform infrared spectroscopy (FTIR), water contact angles and electrochemical methods. The interaction between Tyr enantiomers and the Tei/Cu@Pt/SWCTNs-MoS2 chiral interface was determined via differential pulse voltammetry (DPV). The results exhibited enantioselective interaction between the modified electrodes and Tyr enantiomers, and a stronger interaction was obtained from L-Tyr than D-Tyr. The DPV responses were linearly dependent with concentration in the range of 10.0 μmol·L −1 to 5.0 mmol·L −1, and the limits of detection were 3.2 μmol·L −1 and 4.7 μmol·L −1 for L-Try and D-Tyr (at S/N = 3), respectively. The simple and cost-effective method opens up a new channel for the application of macrocyclic antibiotics.